The Analysis of Sustainable Infrastructure Development Policies in the Citu of Mojokero to Deal with Flood Disasters in the Perspective of Problem Tree Analysis - Multiatul, Yessyrotulk Khafidho; Sutianah , Berlian Ayu Natasha; M. Noer Falaq Al Amin, M. Noer Falaq Al Amin (International Conference on Multidisciplinary Issues (INCOMI), 2024)
This research is motivated by the phenomenon of the natural flood disaster that hit the city of Mojokerto, where later there will be several things done by the Mojokerto city government to overcome the flood disaster. This research is also used to answer the main problem, which is mainly related to sustainable development of Mojokerto city infrastructure. This research uses a qualitative method using literature studies which are used for three analyzes which will later explain and analyze in the form of a there analysis diagram which contains the causes of the problem we have taken, namely the flood disaster. ​Sustainable Development Goals, in Mojokerto Guarantee a healthy life and improve the welfare of all residents of all ages. Floods that occur have impacts such as psychological and health disorders, such as diarrhea and dengue fever.